Progressive muscular dystrophy: Duchenne type. Controversies of the kinesitherapy treatment - Leitão, Ana Valéria de Araujo; Duro, Luiz Alves; Penque, Glória Maria Cardoso de Andrade (São Paulo Medical Journal, 1995)
The authors carried out a study of children with progressive muscular dystrophy of Duchenne type (DMD), giving special attention to physiatrical follow-up, having in mind that the practice of exercises has been debated very much in the specialized literature. The goal of this study is to try to settle the limits for the utilization of kinesitherapy which should be applied only in specific situations, such as: after skeletal muscular trauma or when the respiratory system is at risk. In this situation the physiatrical procedure would be to restrict physical activity, with early use of wheelchairs and the exclusion of the use of orthoses for orthostatism. DMD, at present, has been considered a result of duplication (60%), deletion (5 to 6%) or point mutations at gen Xp21 (Zatz, 1994), that codifies a protein called Dystrophin ( Hoffman et al., 1987). Dystrophin is a cytoskeletal sarcolemmic protein that constitutes about .002% of the total protein of the muscle, present in skeletal fibers concentrated in muscle tendinous joints, which supplies mechanical reinforcement to the surface of the membrane during stretching and shortening physical activity. This protein is absent in DMD cases, wherefore, the sarcolemma undergoes a segmentary necrosis losing its contractile property during eccentric and concentric physical activity. The importance of physiatrical follow-up for DMD patients is to avoid deformities and tendon shortening, to ameliorate the patient’s quality of life, to provide respiratory assistance and general couseling to members of the patient’s family. The objective of this study is to try to clarify the risks and possibilities of kinesitherapy applied to DMD cases.